2021
DOI: 10.1096/fj.202000930r
|View full text |Cite
|
Sign up to set email alerts
|

BAG6 promotes PINK1 signaling pathway and is essential for mitophagy

Abstract: Bcl-2-associated athanogen-6 (BAG6) is a nucleocytoplasmic shuttling protein involved in protein quality control. We previously demonstrated that BAG6 is essential for autophagy by regulating the intracellular localization of the acetyltransferase EP300, and thus, modifying accessibility to its substrates (TP53 in the nucleus and autophagy-related proteins in the cytoplasm). Here, we investigated BAG6 localization and function in the cytoplasm. First, we demonstrated that BAG6 is localized in the mitochondria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The comprehension of PINK1/Parkin-related mitophagy signaling in colon cancer is of emerging interest. Recent evidence described the role of Bcl-2-associated athanogen-6 induced BAG6 as a novel receptor in the PINK1/Parkin pathway involved in protein quality control [ 35 ]. In BAG6-transfected LoVo cells, the mitophagy process was observed after mitochondrial depolarization and phosphorylation-ubiquitination of mitochondrial proteins [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comprehension of PINK1/Parkin-related mitophagy signaling in colon cancer is of emerging interest. Recent evidence described the role of Bcl-2-associated athanogen-6 induced BAG6 as a novel receptor in the PINK1/Parkin pathway involved in protein quality control [ 35 ]. In BAG6-transfected LoVo cells, the mitophagy process was observed after mitochondrial depolarization and phosphorylation-ubiquitination of mitochondrial proteins [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence described the role of Bcl-2-associated athanogen-6 induced BAG6 as a novel receptor in the PINK1/Parkin pathway involved in protein quality control [ 35 ]. In BAG6-transfected LoVo cells, the mitophagy process was observed after mitochondrial depolarization and phosphorylation-ubiquitination of mitochondrial proteins [ 35 ]. On the contrary, the deletion of this nucleocytoplasmic shuttling protein in SW480 cells abolished mitochondrial mass, mitophagy and PINK1 accumulation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to size limitation, only fragmented mitochondria are engulfed into autophagomes [ 48 ]. In basal conditions, BAG6 is located in the mitochondrial matrix; however, after mitochondrial depolarization, it translocates to the OMM and induces mitochondrial fragmentation [ 49 ]. BAG6 also modulates mitochondrial morphology by interacting with the pro-fusion protein MNF2, thus promoting its proteasomal degradation in a cell model where expression of DRP1, a key regulator of fission, is downregulated [ 50 ].…”
Section: Bag Family Members In Mitophagy Regulationmentioning
confidence: 99%
“…BAG2 is also reported to promote mitophagy by inhibiting PINK1 degradation in neurons [ 187 , 188 ], although the role of BAG2 in the heart has not been determined. A recent study demonstrated that BAG6 localizes in the mitochondria matrix but translocates to the MOM after mitochondrial depolarization to enhance PINK1 accumulation at the mitochondria [ 189 ]. In addition, the authors showed that BAG6 functions as a mitophagy receptor by binding to LC3, facilitating mitophagy in cancer cells.…”
Section: Mitochondrial Quality Control By Mitophagymentioning
confidence: 99%